TEORI KEBENARAN PERSPEKTIF FILSAFAT ILMU - Yumesri Yumesri; Ahmad Syukri; Badarussyamsi (Jurnal Genta Mulia, 2024)
Epistemological discussions are more focused on the sources of knowledge (the origin of knowledge) and theories about the truth of knowledge. The first discussion is related to the truth of the philosophy of science, types of philosophical truth of science, criteria for the philosophical truth of science, and the nature of the philosophical truth of science. Meanwhile, the second discussion focuses on the question of whether the "truth" of knowledge can be described with patterns of correspondence, coherence, or practical-pragmatic aspects. Furthermore, discussions in epistemology undergo development, with a focus on the sources of knowledge, processes and methods to obtain knowledge, ways to prove the truth of knowledge, and levels of truth of knowledge. This article attempts to explore the position of knowledge and truth.